210k views
3 votes
Rewrite the equation by completing the square.
x^2 + 2x – 48 = 0

2 Answers

2 votes

Answer:

(x+1)^2=49

Explanation:

User Mahmoud Moravej
by
5.4k points
3 votes

Answer:

(x+1)^2 = 49

x = 6 x = -8

Explanation:

x^2 + 2x – 48 = 0

Add 48 to each side

x^2 + 2x =48

Take the coefficient of x

2

Divide by 2

2/2=1

Square it

1^2 =1

x^2 + 2x +1=48+1

x^2 +2x+1 = 49

(x+1)^2 = 49

Take the square root of each side

sqrt((x+1)^2) =±sqrt( 49)

x+1 = ±7

Subtract 1 from each side

x+1-1 = -1 ±7

x = -1+7 x = -1 -7

x = 6 x = -8

User Akram Chauhan
by
5.3k points